2022
DOI: 10.1002/jmv.27862
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological alteration of symptoms with serotype among dengue infected pediatric patients

Abstract: Dengue fever is a self-limiting, acute febrile illness caused by an arbovirus. This infection may be asymptomatic or symptomatic with its potential lifethreatening form as DHF/DSS. Severe dengue cases occur typically in children due to overproduction of proinflammatory and anti-inflammatory cytokines (called cytokines storm) as well as increased microvascular permeability in them.This study aimed to find circulating dengue serotype and their clinicopathological association among pediatric patients admitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
2
3
0
2
Order By: Relevance
“…Also, acute phase symptoms were more commonly observed in PCR-positive patients in the present study. This observation is similar to the observation made by Verma et al [ 37 ]. The data relating to acute phase symptoms presented in NS1-positive patients related to PCR positivity were not statistically significant due to higher p values, which might be related to the small sample size.…”
Section: Discussionsupporting
confidence: 93%
“…Also, acute phase symptoms were more commonly observed in PCR-positive patients in the present study. This observation is similar to the observation made by Verma et al [ 37 ]. The data relating to acute phase symptoms presented in NS1-positive patients related to PCR positivity were not statistically significant due to higher p values, which might be related to the small sample size.…”
Section: Discussionsupporting
confidence: 93%
“…21 Neurological complications like fits, altered sensorium and irritability was observed incidentally by the study conducted in India. 18 The classical hematological findings reported in dengue infection are thrombocytopenia, leucocytopenia, and hemoconcentration found in 13,14 and Jayadas TTP et al 22 On the contrary we found no significant increase in hemoconcentration apart from leucopenia and thrombocytopenia, similarly seen with Phakhounthong et al 11 Some studies showed Leukocytosis with increase hemoconcentration and thrombocytopenia Nandwani S etal. 23 In our study thrombocytopenia was most common finding in those with severe dengue, likewise with Tanner L et al 24 Thrombocytopenia and sudden fall in total leukocytes counts in early phase of illness was the predictor of severe dengue reported from a study conducted in Sri Lanka, Kularatirum et al 25 Deranged liver functions LFTs in the form of raised AST (aspartate aminotransferase) and ALT (alanine transferase) and low albumin was observed by Sri Lankan study 22 , though hepatomegaly was noted but LFTs were not included in our study.…”
Section: Discussionsupporting
confidence: 63%
“…Abdullah et al 13 , Saiful Islam et al 14 & Afroze S et al 15 In addition to above findings Amjad Mehmood et al 16 observed retrobulbar pain with headache. The most important parameter in predicting dengue shock syndrome was poor capillary refill time, pleural effusion, ascites and thrombocytopenia similarly observed by Phakhounthong et al 11 Srikiatkhachorn et al 17 demonstrated thrombocytopenia with plasma leakage were associated with dengue severity whereas hypotension was documented with SD (Severe Dengue) by Saiful Islam et al 14 The most common bleeding manifestations in DSS were epistaxis, petechiae, gum bleed followed by gastrointestinal bleed in the form of melena and hematemesis, similarly seen with Kang Zhuang Yuan et al 10 Petechiae was noted by Verma P et al 18 , on the other hand melena was observed with Potts JA et al 19,20 In addition to above clinical signs, gall bladder thickness was observed with Tauqeer HM. 21 Neurological complications like fits, altered sensorium and irritability was observed incidentally by the study conducted in India.…”
Section: Discussionmentioning
confidence: 85%
“…Estudos relatam a importância de manifestações clínicas como sangramento da mucosa, vômitos persistentes, na previsão do tempo para progresão grave da doença. Com isso seu reconhecimento precoce e o monitoramento rogoroso dessas manifestações clínicas, juntamento com um tratamento adequado, podem significar a diferença entre o sucesso e o fracosso terapêutico em crianças com infecção por dengue (VERMA et al, 2022).…”
Section: )unclassified
“…Suas descobertas implicam na necessidade de maior vigilância e complementação de outros estudos de desfechos clínicos da dengue. A marca registrada da dengue grave, particularmente na faixa etária mais jovem, é a permeabilidade vascular levando ao extravasamento de plasma e subsequente choque circulatório e suas consequências, que podem ser fatais (VERMA et al, 2022).…”
Section: )unclassified